The Civil Rights Litigation Clearinghouse: Origins and Goals - Schlanger, Margo (KULA, 2018)
The Civil Rights Litigation Clearinghouse (http://clearinghouse.net) solves a significant information deficit related to civil rights litigation by posting information about thousands of ongoing and closed large-scale civil rights cases. Documents are OCR’d and searchable; cases are searchable by metadata tags as well as full-text searching. Each case has a litigation summary by a law student. We live in a civil rights era—a time when people are using the courts, among other strategies, to fight for civil rights. The Clearinghouse posts the records of those fights, the stories of civil rights cases—across topics, across regions, across organizations—and makes them searchable, usable, and available to everybody.